Doctor Who. The complete fourth series [videorecording (DVD)] - Strong, James (Television director); Tennant, David, 1971-; Tate, Catherine; Piper, Billie, 1982- (BBC Worldwide, 2012)
The Doctor and Donna Noble travel back to Pompeii in AD 79 on the eve of the infamous eruption, investigate a series of grisly murders with the help of Agatha Christie, journey to the homeworld of the sinister Ood, face an old enemy of the Doctor's, and more.